El Proyecto corpus vasorum Hispanorum: principales resultados - bustamante álvarez, macarena (Rei Cretariae Romanae Fautorum Acta, 2024)
The results of a research project focused on the analysis of precocturam epigraphic marks on Hispanic terra sigillata located in the Lusitania province are presented. This study was based on an exhaustive compilation of data both from museums and archaeological sites, giving priority to those that had contextual data. To manage the data, an online and open real-time database was developed. This platform had a specific template for each of the pieces containing morphological, contextual, chronological data and graphic documentation. Additionally, this project included an analytical component, using archaeometric methods that helped to confirm some production centers in the region. As a result, this study has contributed to redefining the commercial, epigraphic and anthroponymic landscape of a production on a topic, that of the sigilla, an area that had not been extensively evaluated previously.